Biomarkers and long-term labour market outcomes: the case of creatine - Böckerman Petri; Bryson Alex; Viinikainen Jutta; Hakulinen Christian; Pulkki-Raback Laura; Raitakari Olli; Pehkonen Jaakko (Institute for the Study of Labor (IZA), 2022)
Using the Young Finns Study (YFS) combined with the Finnish Linked Employer-Employee
Data (FLEED) we show that quantities of creatine measured in 1980 prior to labour market
entry affect labour market outcomes over the period 1990-2010. Those with higher levels of
creatine (proxied by urine creatinine) prior to labour market entry spend more time in the
labour market in the subsequent two decades and earn more. Creatine is not associated with
high educational attainment. The associations between creatine and labour market outcomes
are robust to controlling for other biomarkers, educational attainment and parental
background. Creatine is a naturally occurring nitrogenous organic acid which supplies energy
to body cells, including muscles. Our findings are consistent with high energy levels, induced
by creatine, leading to productivity-enhancing traits such as a high propensity for effort,
perseverance, and high-commitment.